Menggali Potensi Fitrah Anak Didik: Kajian Konseptual tentang Hakikat Manusia dalam Pendidikan - Ahmad Mudzakkir; Maemunah; Yuspiani; Alwan Suban; Suarni (South Sulawesi Education Development, 2025)
This article explores the essence of students as pedagogical beings based on the Islamic concept of fitrah. The study aims to elaborate the role of innate potential and divine learning instruments—hearing, sight, and heart—as foundational elements in education. Using a conceptual and literature-based approach, the findings indicate that education should nurture rather than impose, optimizing natural human tendencies. The discussion confirms the novelty of fitrah-based pedagogy as an integrative model grounded in theology, humanism, and contemporary pedagogical thought.